2022
DOI: 10.3389/fimmu.2022.831279
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Errors of Immunity Associated With Type 2 Inflammation in the USIDNET Registry

Abstract: BackgroundMonogenic conditions that disrupt proper development and/or function of the immune system are termed inborn errors of immunity (IEIs), also known as primary immunodeficiencies. Patients with IEIs often suffer from other manifestations in addition to infection, and allergic inflammation is an increasingly recognized feature of these conditions.MethodsWe performed a retrospective analysis of IEIs presenting with allergic inflammation as reported in the USIDNET registry. Our inclusion criteria comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The rapid pace of IEI gene discovery also poses a logistical challenge for maintaining TGP content relevance. In the time between the initial design of our TGPs and the submission of this manuscript, at least 40 more monogenic IEIs have been identified in patients with clinical diagnoses of CVID [17], another 43 in conjunction with IBD phenotypes [18], and at least 20 more genes for HIES or CMC-related phenotypes [19,135,136] (Tables S3). Genes already in the IUIS nosology have also been re-classifiedmost notably, TYK2 from HIES to MSMD and DOCK8 to CID [1].…”
Section: Many Of Our Index Patients Did Not Present With the Most 'Ca...mentioning
confidence: 99%
“…The rapid pace of IEI gene discovery also poses a logistical challenge for maintaining TGP content relevance. In the time between the initial design of our TGPs and the submission of this manuscript, at least 40 more monogenic IEIs have been identified in patients with clinical diagnoses of CVID [17], another 43 in conjunction with IBD phenotypes [18], and at least 20 more genes for HIES or CMC-related phenotypes [19,135,136] (Tables S3). Genes already in the IUIS nosology have also been re-classifiedmost notably, TYK2 from HIES to MSMD and DOCK8 to CID [1].…”
Section: Many Of Our Index Patients Did Not Present With the Most 'Ca...mentioning
confidence: 99%
“…While the extent to which the atopic phenotypes observed in LOF mutations in the CBM complex are explained by disrupting downstream NF-κB signaling is not clear, a retrospective analysis of patients with IEI registered in the USIDNET revealed that more than half of patients with NF-κB Essential Modulator ( NEMO , also known as IKBKG ) deficiency were noted to have atopic dermatitis ( 67 ). A more recent analysis of eosinophilia and elevated IgE in the USIDNET revealed that 3 out of 3 patients with NFKB2 defects had at least one atopic manifestation and eosinophilia above the upper limit of normal in the reference population and an increased proportion of patients with IKBKG defects had both eosinophilia and elevated IgE ( 68 ).…”
Section: Aberrant Tcr Signalingmentioning
confidence: 99%
“…Patients with IEI may first present with signs of immune dysregulation, which can precede symptoms or lab findings indicative of immunodeficiency (5)(6)(7). These can include autoimmune or atopic manifestations.…”
Section: Introductionmentioning
confidence: 99%